2021
DOI: 10.3389/fevo.2021.727471
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Olfactory Biases of Male Euglossine Bees: Species-Specific Antennal Responses and Their Evolutionary Significance for Perfume Flowers

Abstract: Male euglossine bees exhibit unique adaptations for the acquisition and accumulation of chemical compounds from “perfume flowers” and other sources. During courtship display, male bees expose perfume mixtures, presumably to convey species-specific recognition and/or mate choice signals to females. Because olfaction regulates both signal production (in males) and signal detection (in females) in this communication system, strong selective pressures are expected to act on the olfactory system, which could lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…Consequently, pollination systems of unisexual flowers could ensure pollen transfer for the host plant through the similarity of the floral scents, which should guarantee a floral constancy of the pollinators [ 15 , 28 ]. Thus, the occurrence of sexually mono- and dimorphic scent patterns within the genus Catasetum might reflect the distinct selective pressures as a consequence of olfactory/behavioural biases of specific euglossine pollinators [ 10 , 17 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, pollination systems of unisexual flowers could ensure pollen transfer for the host plant through the similarity of the floral scents, which should guarantee a floral constancy of the pollinators [ 15 , 28 ]. Thus, the occurrence of sexually mono- and dimorphic scent patterns within the genus Catasetum might reflect the distinct selective pressures as a consequence of olfactory/behavioural biases of specific euglossine pollinators [ 10 , 17 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…52,53,[73][74][75]97 Linalool (37) has also been conrmed to be active in eld bioassays to the euglossine bee pollinators of several perfume rewarding orchids. 94,[98][99][100] Terpenoids 38 and 39 have also been conrmed as behaviourally active to the male Eulama euglossine bee pollinator of the orchid Sarcoglottis acaulis in eld studies. Interestingly, in this case the typical perfume collecting behaviour was not observed at either the orchid ower or the chemical baits, and instead pollinators appeared to forage for nectar, despite the specic attraction of males.…”
Section: Monoterpenesmentioning
confidence: 99%
“…94 More recently, this isomer has also been shown to elicit strong antennal responses from many other species of perfume-collecting bees across several genera. 98 The related 1,2,4-trimethoxybenzene (59) has also been shown to elicit antennal responses in several perfume-collecting bee species. 98,113 Outside of perfume rewarding systems, Salzmann et al 141 found that the volatile prole of the bumblebee-pollinated Anacamptis coriophora was dominated by benzenoids, most notably 58 and 4-methoxybenzaldehyde.…”
Section: Benzenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact role of orchid bee perfume is unknown, previous works showed evidence about its importance as a sexual signaling trait involved in the reproductive isolation of species on sensory Mitko et al 2016;Brandt et al 2021), behavioral (Eltz et al 2008), and macroevolutionary scale (Zimmermann et al 2009;Weber et al 2016). Terpenes, aromatics and other organic compounds make up the bouquets and have demonstrated its role as highly specialized signaling markers at the species level (Eltz et al 2006;Eltz et al 2008).…”
Section: Introductionmentioning
confidence: 99%